An intense SFE & SSC event in geomagnetic H,Y,Z fields at the Indian chain of observatories - Rastogi, R.G.; Rao, D.R.K.; Alex, S.; Pathan, B.M. (My University, 1997)
Changes in the three components of geomagnetic field are reported at the chain of ten geomagnetic observatories in India during an intense solar crochet that occurred at 1311 h 75° EMT on 15 June 1991 and the subsequent sudden commencement (SSC) of geomagnetic storm at 1518 h on 17 June 1991. The solar flare effects (SFE) registered on the magnetograms appear to be an augmentation of the ionospheric current system existing at the start time of the flare. An equatorial enhancement in ΔH due to SFE is observed to be similar in nature to the latitudinal variation of SQ (H) at low latitude. ΔY registered the largest effect at 3.6° dip latitude at the fringe region of the electrojet. ΔZ had positive amplitudes at the equatorial stations and negative at stations north of Hyderabad. The SSC amplitude in the H component is fairly constant with latitude, whereas the Z component again showed larger positive excursions at stations within the electrojet belt. These results are discussed in terms of possible currents of internal and external origin. The changes in the Y field strongly support the idea that meridional current at an equatorial electrojet station flows in the ionospheric dynamo, E.
Keywords: Geomagnetic storms; Ionospheric dynamo; SSC; Solar flare effect